2017
DOI: 10.1590/0104-530x2512-16
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de redes de instituições de pesquisa científica e tecnológica baseada em um sistema de gestão padronizado

Abstract: Resumo: A intervenção em um fenômeno como um Sistema Nacional de Inovação (SNI) é algo complexo, principalmente em economias em desenvolvimento. Estudos constatam a ausência de instrumentos e ações práticas Abstract:The interference in a phenomenon as a National Innovation System (NIS) is complex, especially in developing economies. Some studies discuss the absence of tools and practical actions that allow a continuous improvement of these systems. In Brazil, there is a case of pioneering action developed by E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 19 publications
0
5
0
3
Order By: Relevance
“…The Taguchi analysis showed that the optimal conditions for the phytoremediation process are concentrations of nitrate and phosphate ions high range (400 mg L -1 , 300 mg L -1 ), mid-range COD (830 mg L -1 ) and in an HRT of 21 days. Ijaz, A., Imran, A., ul Haq, M.A., Khan, Q.M., Afzal, M., (2016). Phytoremediation: recent advances in plant-endophytic synergistic interactions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The Taguchi analysis showed that the optimal conditions for the phytoremediation process are concentrations of nitrate and phosphate ions high range (400 mg L -1 , 300 mg L -1 ), mid-range COD (830 mg L -1 ) and in an HRT of 21 days. Ijaz, A., Imran, A., ul Haq, M.A., Khan, Q.M., Afzal, M., (2016). Phytoremediation: recent advances in plant-endophytic synergistic interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Dawkins (2016) conta que há vários memes: melodias, músicas, ideias, slogans, frases de efeito, jargões, ditados populares, modas do vestuário, boas práticas, regras de etiqueta, conceitos, métodos, teorias, técnicas, entre outras manifestações. O autor afirma que até um padrão arquitetônico, como uma ponte em arcos ou uma ponte com cordas de aço, é uma manifestação memética.…”
Section: A Biologia E O Comportamentounclassified
See 3 more Smart Citations